Peningkatan Panjang Pod dan Hasil Kacang Panjang (Vigna unguiculata ssp. sesquipedalis L.) melalui Seleksi Pukal dalam Generasi yang Ketujuh - Annur Syakirah Shamsul Azman (2020)
Snake bean or Vigna unguiculata is a popular tropical vegetable in Malaysia. Snake bean contains high nutritional contents such as fiber, protein, vitamins and minerals and has a high demand in this country especially to be consumed in daily meals. In getting a high quality of yield for this snake bean, a research of studying the improvement of pod length and yield through mass selection was done. Mass selection is one of plant breeding techniques in improving the quantity and quality of the plant. The selections of snake bean have been continuously done for several generations. The purpose of this study is to continue the selection of snake bean for the 7th generation where the longest pod and the highest yield was selected. The vegetative and generative growth of snake bean was observed, and the data was collected. There were 225 seeds planted in 9 beds where the size for each bed was 9-meter length X 1-meter width. The location of the planted snake bean was in Agro Techno Park in UMK Jeli Campus. The results of the study were tested by descriptive statistical analysis to show the maximum, mean and standard deviation of pod length. The results of this research explained that the further the generation, the longer the pod length and yield performance in snake bean population.